Structure of the Roses Gene Pool of the M.M. Gryshko National Botanical Garden of NAS Ukraine - Rubtsova, Olena Leonidivna; Koval, Inna; Chizhankova, Valentina; Buidina, Tetyana; Sokolova, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
In article offered the characteristic of the gene pool of the M.M. Gryshko National Botanical Garden of NAS of Ukraine. Main sources of introduction of cultivars of Rosa L. are defined. Information on the beginning, methods and results of introduction is provided. The gene pool collection of roses, that comprises 27 species, 11 forms and 515 cultivars and has the status of the National property, is described by morphotypes, garden groups, countries of origin, the colour of flowers and by the years of breeding. As the result it was defined that the distribution of cultivars by the garden groups corresponds to the composition of the world collection of roses, the larger part of the collection is comprised of cultivars of foreign origin, the main part of the collection is composed by the tea-hybrid roses of pink colour. Main directions of further researches on introduction and selection of roses are outlined.